Therapeutic Interventions for Mental Wellness in Correctional Facilities: A Systematic Review - Criss, Jhala (International journal of offender therapy and comparative criminology, 2025)
The article includes a systematic review of therapeutic interventions being used to improve mental health of males and females incarcerated in U.S. jails and prisons. Using pertinent keywords, we searched the following databases: SocINDEX, CINAHL Complete, Medline Complete, PsychINFO, Psychology and Behavioral Sciences Collection, and Criminal Justice Abstracts with Full Text for studies published between 2010 and 2021. The initial search yielded 9,622 articles. After screening, 28 articles met the inclusion criteria and were reviewed. Review indicated use of a diverse range of interventions to address mental health outcomes including, but not limited to, PTSD, depression, and anxiety. A few studies did not focus on specific mental health outcomes, but rather on behavioral outcomes such as distress, affect, mood, time spent in the hospital, number of acts of self-injury, competency restoration, and wellbeing of the participants. The review includes implications for future research and practice.